Inherent multiculturalism: An ancient Chinese practice becomes a part of the Indonesian everyday - CHAN, Margaret (Institutional Knowledge at Singapore Management University, 2018)
Several methods are used to trace cultural transfer between countries. The time-honoured methods are chronicles of early travellers and archaeology. We can also look to epigraphs and loan words. Present-day ethnic communities also suggest earlier settlements. Edward B. Tylor proposed the world distribution of games as anthropological evidence. Tylor's method combined with an archaeology into the Everyday provides evidence of earlier cultural transfer and present-day applications of the game enables analysis to draw socio-cultural knowledge of inter-ethnic, inter-cultural reception to foreign influences in host societies.